Effect of quercetin on the uptake and efflux of aristolochic acid I from Caco-2 cell monolayers. (11th May 2016) - Kimura, Osamu; Fujii, Yukiko; Haraguchi, Koichi; Ohta, Chiho; Koga, Nobuyuki; Kato, Yoshihisa; Endo, Tetsuya
Abstract: Objective: The purpose of this study was to determine whether quercetin decreases the uptake of aristolochic acid I (AAI) from the apical membranes of Caco-2 cells via H + -linked MCTs at neutral pH as well as to confirm the secretion of AAI through the Caco-2 cell monolayers via ABC transporters. Methods: Caco-2 cells cultured on the dishes or permeable membranes were incubated with AAI in the absence or presence of quercetin or transporter inhibitors. Key findings: Coincubation with quercetin decreased the uptake of AAI by Caco-2 cells cultured on the dishes at pH 7.4, and a similar decrease in AAI uptake was found when the cells were coincubated with acetic acid or benzoic acid. In contrast, the basolateral-to-apical transport of AAI was higher than the apical-to-basolateral transport of AAI at pH 7.4, and the former transport was decreased by quercetin and the BCRP inhibitors of Ko-143 and mitoxantrone, but not by P-gp or MRP2 inhibitors. Conclusions: AAI appears to be secreted from the apical membranes of Caco-2 cells via BCRP at neutral pH, although a small amount of AAI is taken up from the apical membranes via H + -linked MCTs, and quercetin may decrease both the BCRP-mediated efflux and the MCT-mediated influx of AAI.